Ultrafast optical switching for polyarylates with allylic groups by Nd:YAG Sagnac interferometer - Ciołek, Rafał; Ratusznik, Grzegorz J.; Świłło, Rafał; Pura, Bronisław; Zadrożna, Irmina; Piramidowicz, Ryszard; Kaczorowska, Ewa; Zagórski, Alfred (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
In this paper, an ultrafast optical switching for thin polymer films (polyarylans with allylic groups) is presented. It was realized using the Nd:YAG Sagnac interferometer. Investigated polymers appeared to be suitable candidates for elements of integrated optical telecommunication systems.
Optica Applicata, Vol. 36, 2006, nr 2-3, s. 381-387
Keywords: optyka; optical materials; polymers; optical switches; nonlinear optics